Assessment of Runway ACN-PCN Compatibility at Djalaluddin Gorontalo Airport - Sri Susanty Satya A Dukalang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Air transport infrastucture plays a vital role in regional economic development particularly in Eastern Indonesia where airport facilities are limited. Djalaluddin Airport in Gorontalo serves as the primary gateway connecting the region to major Indonesian cities. With increasing aircraft movement and changes in fleet composition, assessing the compatibility between aircraft loads and runway strength has become essential. The study purpose was to evaluate the pavement capacity of Djalaluddin Airport using the Aircraft Classification Number-Pavement Classification Number (ACN-PCN) method recommended by the International Civil Aviation Organization (ICAO). As air traffic continues to grow, understanding the structural adequacy of airport pavements ensures both safety and sustainability. Materials and methods. A technical feasibility study approach was adopted based on ICAO and FAA standards. Data on operational aircraft, including ATR 72-600 and Boeing 737-800, were obtained through coordination with airport authorities and field observation. ACN values were taken from ICAO and FAA reference tables, assuming flexible pavement and medium subgrade strength (CBR 6-10%). The estimated PCN was derived from empirical correlations considering pavement thickness (55-60 cm) and subgrade conditions typical of Gorontalo lateritic soils. Compatibility was assessed under the ICAO criterion that aircraft operation is permissible only when ACN ≤ PCN. Results. The findings show that ATR 72-600 (ACN ≈ 18) operates safely within the estimated pavement capacity (PCN ≈ 30) while Boeing 737-800 (ACN ≈ 50) exceeds the allowable limit, indicating potential overloading. Runway geometry (2500x45m) satisfies ICAO Code C requirements. These results emphasize the need for periodic PCN evaluations at regional airports to prevent premature pavement deterioration. Conclusions. The study concludes that the existing runway at Djalaluddin Airport is structurally adequate for regional turboprop operations but insufficient for frequent jet aircraft such as the Boeing 737. Regular ACN-PCN evaluations are recommended to ensure continued operational safety and guide infrastructure planning across Indonesia’s smal and regional airports.